إستراتيجية الإعلام الأمني وآليات ترسيخ ثقافة التوعية والوقاية المرورية - عطوي, مليكة; مقيدش, إيمان هاجر (University of Eloued جامعة الوادي, 2018)
يهدف هذا المقال إلى محاولة إبراز دور الإعلام في تحقيق التوعية المرورية والعلاقة القائمة بين الإعلام والأمن والجهود المتكاملة بينهما في التخفيض من ظاهرة حوادث المرور، وذلك من خلال التركيز على الاستراتيجيات التي تتبناها الأجهزة الأمنية في تعاملها مع وسائل الإعلام كآليات مساهمة في ترسيخ ثقافة التوعية المرورية لدى الشباب السائقين بولاية سطيف عموما والوقاية من حوادث المرور على وجه الخصوص. Abstract : This article aims at trying to highlight the role of media in achieving traffic awareness and the relationship between media, security and integrated efforts to reduce the phenomenon of traffic accidents by focusing on the strategies adopted by the security services in dealing with the media as mechanisms that contribute to the establishment of a culture of traffic awareness among young drivers in the Wilaya of Setif in general and the prevention of traffic accidents in particular.
The strategy of the security media and the mechanisms of establishing a culture of awareness and prevention of traffic
مجلة البحوث والدراسات المجلد 15 العدد01 جامعة الوادي
Keywords: الاستراتيجية; الإعلام الأمني; التوعية المرورية; الوقاية المرورية ; حوادث المرور.; Strategy - Security Media - Traffic Awareness - Traffic Prevention - Traffic Accidents.